2021
DOI: 10.1371/journal.pone.0252529
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and perceived delays for diagnosis and staging of lung cancer in Portugal: A nationwide survey analysis

Abstract: Background We aimed to identify the perception of physicians on the limitations and delays for diagnosing, staging and treatment of lung cancer in Portugal. Methods Portuguese physicians were invited to participate an electronic survey (Feb-Apr-2020). Descriptive statistical analyses were performed, with categorical variables reported as absolute and relative frequencies, and continuous variables with non-normal distribution as median and interquartile range (IQR). The association between categorical variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
(46 reference statements)
1
3
1
Order By: Relevance
“…In most Portuguese institutions, the results take 14–21 days, 1 week longer than international guidelines recommend. These data are in agreement with another Portuguese study of lung cancer, which reported a median waiting time for the results of biomarker assays of 17.9 days [ 54 ]. Lim et al.…”
Section: Discussionsupporting
confidence: 92%
“…In most Portuguese institutions, the results take 14–21 days, 1 week longer than international guidelines recommend. These data are in agreement with another Portuguese study of lung cancer, which reported a median waiting time for the results of biomarker assays of 17.9 days [ 54 ]. Lim et al.…”
Section: Discussionsupporting
confidence: 92%
“…In a study of 1330 patients with lung cancer by Fernandez et al, the mean diagnosis time was found to be 19.8 ± 13.9 days [14]. In a recent survey analysis, the median time to diagnosis in cancer patients was found to be 11.05 days [15]. In our study, the diagnosis time and delay were found to be quite high compared to the literature, especially in malignant patients.…”
Section: Discussioncontrasting
confidence: 51%
“…Timely management standards for lung cancer have been established by some countries [ [18] , [19] , [20] , [21] , [22] ], but these standards are not well supported by evidence and are based mainly on expert consensus. Discrepancies exist between the recommendations and current practice.…”
Section: Discussionmentioning
confidence: 99%